A Study on Serum Calcium Level in Resistant Hypertension - Dangal, Binod; Shakya, Yogendra Man; Narayan, Prasad Pratap; Shakya, Yagya Laxmi; Shrestha, Tirtha Man; Murti, Anil Om (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Hypertension is one of the common public health problem in the world and gradually increasing in Nepal. Serum calcium level has shown to be associated with cardiovascular disease. Disturbed calcium metabolism plays important role in pathogenesis of essential hypertension.Methods: Four hundred people including 200 normotensives and 200 hypertensives were enrolled in the study, their blood pressure and total serum calcium were measured. Hypertensive group was divided into two: Hypertensives on Calcium channel blockers (CCBs) and hypertensive other than CCBs. Serum Calcium level was measured with calcium-O- Cresopthalein complex(OCPC) reaction. All other baseline investigations including blood sugar, renal function tests, complete blood counts, thyroid function tests were done to exclude secondary causes in hypertensive group. Statistical analysis was done using SPSS version 21. Differences between the groups were analyzed with independent “t” test.Results: Significant difference in serum calcium level was found in between normotensive and hypertensive. Difference in serum calcium level between hypertensive on CCBs and hypertensive other than CCBs were insignificant.Conclusion: Significantly reduced serum calcium level is found in hypertensive individuals as compared to normotensive group. Lower level of serum calcium level affects the blood pressure. Essential Hypertension is associated with significant familial predisposition.